Integrating Digital Literacy Into English As A Foreign Language (EFL) Class: A Cooperative Learning Approach - Henny Mardiah (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, Publikasi, 2022)
In this ICT (Information, Communication and Technology) era in which internet service spreads widely over the world enables people to access abundant information more easily. Digital literacy skills are crucially needed to filter reliable and unreliable information. Digital literacy competencies are also essential to filter the massive spread of fake news or hoax and hate speech. In education, digital literacy competencies need to be taught and trained to students to gain information, analyse digital information content critically and to use information in many types of formats from a number of sources obtained through computers. Therefore, digital literacy skills can be integrated in learning. Cooperative learning is a learning approach that allow students take part in group learning activities to analyze, synthesize and reflect thoughtful evaluation of a digital content. This study aims to foster integration of digital literacy competencies into English as a Foreign Language (EFL) class through cooperative learning approach. The subjects of this study were 37 students of 6th semester of TBI-1 (English Education Department) class of the State Islamic University of North Sumatera. This study was conducted using qualitative method. Data collection techniques utilized secondary research and observation. The research findings show that students who are dominated by Generation Z are literate enough in performing digital literacy skills through cooperative learning approach.